Evaluation of phototoxic potential of aerial components of the fig tree against human melanoma - Conforti, F. (Cell Prolif, 2012)
OBJECTIVES: To date, Ficus carica L. cultivar Dottato (F. carica) has not been studied from a phototoxic point of view. In the present work, aerial components of F. carica from Italy, were examined to assess their antioxidant and phototoxic activity on human melanoma cells. A relationship between antioxidant, phototoxic activities and chemical composition has also been investigated. MATERIALS AND METHODS: Coumarin and fatty acid content in F. carica leaves, bark and woody parts were examined and compared by capillary GC and GC/MS. Polyphenolic content was also determined. Linoleic acid peroxidation and DPPH test were used to assess antioxidant activities, and MTT assay was used to evaluate anti‐proliferative activity, on C32 human melanoma cells, after irradiation with a UVA dose of 1.08 J/cm(2). RESULTS: Leaves demonstrated the best antioxidant and anti‐proliferative activity in comparison to bark and wood. In particular, leaves were shown to possess the highest anti‐radical activity and inhibition of peroxidation, with IC (50) values of 64 and 1.48 μg/ml respectively. The leaves had highest anti‐proliferative activity with IC (50) value of 3.92 μg/ml. The phytochemical investigation revealed different composition between the coumarins, psoralen and bergapten, fatty acids, polyphenols and flavonoid content among plant parts. CONCLUSIONS: Data obtained indicate that this type of fig tree may constitute an excellent source of bioactive compounds, such as phenolics, coumarins and fatty acids. This study offers a new perspective in developing others formulations potentially useful in photodynamic therapy for treatment of non‐melanoma skin cancers.